Endosomal H(2)O(2) production leads to localized cysteine sulfenic acid formation on proteins during lysophosphatidic acid-mediated cell signaling - Klomsiri, Chananat (2014)
Lysophosphatidic acid (LPA) is a growth factor for many cells including prostate and ovarian cancer-derived cell lines. LPA stimulates H(2)O(2) production which is required for growth. However, there are significant gaps in our understanding of the spatial and temporal regulation of H(2)O(2)-dependent signaling and the way in which signals are transmitted following receptor activation. Herein, we describe the use of two reagents, DCP-Bio1 and DCP-Rho1, to evaluate the localization of active protein oxidation after LPA stimulation by detection of nascent protein sulfenic acids. We found that LPA stimulation causes internalization of LPA receptors into early endosomes that contain NADPH oxidase components and are sites of H(2)O(2) generation. DCP-Rho1 allowed visualization of sulfenic acid formation, indicative of active protein oxidation, which was stimulated by LPA and decreased by an LPA receptor antagonist. Protein oxidation sites colocalized with LPAR1 and the endosomal marker EEA1. Concurrent with the generation of these redox signaling-active endosomes (redoxosomes) is the H(2)O(2)- and NADPH oxidase-dependent oxidation of Akt2 and PTP1B detected using DCP-Bio1. These new approaches therefore enable detection of active, H(2)O(2)-dependent protein oxidation linked to cell signaling processes. DCP-Rho1 may be a particularly useful protein oxidation imaging agent enabling spatial resolution due to the transient nature of the sulfenic acid intermediate it detects.